2016
DOI: 10.5380/rf.v46i1.39625
|View full text |Cite
|
Sign up to set email alerts
|

GERMINAÇÃO E CRESCIMENTO INICIAL DE Machaerium brasiliense VOGEL (FABACEAE) EM CASA DE VEGETAÇÃO

Abstract: ResumoMachaerium brasiliense Vogel é uma espécie arbórea, conhecida popularmente como pau-sangue, jacarandá-bico-de-pato e sapuva. Com o objetivo de verificar a germinação, sementes de M. brasiliense foram mantidas sob temperatura de 20°, 25° e 30 °C, em câmara de germinação com fotoperíodo de 12h ou escuro contínuo. Para análise do crescimento inicial, avaliaram-se, aos 90, 180, 270 e 360 dias após o transplante (DAT), a altura, o comprimento da raiz, a massa seca da parte aérea, da raiz e total e o número de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The nodules present in the roots of L. cultratus were rounded protrusions occurring in lateral roots, which was also observed by Pastorini et al (2016)…”
Section: Arbuscular Mycorrhizal Colonization and Root Nodulationsupporting
confidence: 58%
See 1 more Smart Citation
“…The nodules present in the roots of L. cultratus were rounded protrusions occurring in lateral roots, which was also observed by Pastorini et al (2016)…”
Section: Arbuscular Mycorrhizal Colonization and Root Nodulationsupporting
confidence: 58%
“…The nodulation occurred spontaneously, and no inoculation procedure was performed. Pastorini et al (2016) reported that Machaerium brasiliense Vogel presented nodules only after 180 days. The authors also mentioned that root nodulation is a characteristic of Fabaceae, and that information about nodulation capacity of most native trees is still lacking.…”
Section: Arbuscular Mycorrhizal Colonization and Root Nodulationmentioning
confidence: 99%
“…The variability identified among the accessions is important in the identification of pepper plants with ornamental potential. Accession UFPB134 is recommended when it comes to seedling traits since it presented high performance for seedling height and cotyledons leaf length, forming vigorous seedlings suitable for transplanting, which in turn allows greater success in establishing the plant and maximizes its growth by decreasing the time of transplantation to the field, according to Pastorinil et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…Again, this effect is given by the inhibitory action of the vitamin on the development of seedlings, causing stress to the physiological system. In this stressful condition, different plant species, including coffee, tend to invest in root development at the expense of shoot development as a survival strategy (Pastorini et al, 2016). However, as observed for RSR, this effect can increase the survival rate of seedlings after transplanting, as a larger root system results in greater soil exploration capacity and, consequently, greater capacity to absorb nutrients and water (Ferreira et al, 2012).…”
Section: Resultsmentioning
confidence: 99%